Mineral–mediated multiple defect g–C3N4 for enhanced peroxide photoactivation: Insights into defect synergy and selective removal of electron–rich pollutants - Jie Wang; Yanbai Shen; Sikai Zhao; Ruixue Ma; Haiyi Lv; Cong Han; Wenbao Liu; Baoyu Cui (Chemical Engineering Journal, 2026)

Flexible coaxial dielectric-barrier discharge wire for rapid and versatile chemical and biological decontamination on complex surfaces - Yawen Yang; Shuang Xue; Hexi Li; Zhihao Yi; Shitong Han; Lingce Kong; Dandan Liu; Hui Hua; Ruixue Wang; Anna Zhu (Journal of Environmental Chemical Engineering, 2026)

Chlorine dioxide-mediated aging of polystyrene microplastics - Ruixue Li; Linyong Zhi; Cuiming Huang; Shunli Xiao; Han Gong; Jun Wang (Journal of Environmental Chemical Engineering, 2026)

Crop root response involvement in yield formation under organic substitution: A global meta-analysis - Yue Liu; Hao Ren; Yaru Zhang; Ruixue Chen; Yandong Wang; Juan Han (European Journal of Agronomy, 2026)

Molecular disruption of neuroinflammatory and metabolic pathways mediates triclosan-induced depressive-like behavior in zebrafish - Danting Wang; Junping Liu; Ruixue Zhou; Bing Han; Chunxia Chen; Wentong Meng; Li Qin; Limei Sun; Bin Tan; Chunyan Huang (Toxicology and Applied Pharmacology, 2026)

Liraglutide Promoted Osteogenic Differentiation of Dental Pulp Stem Cells via H3K18 Lactylation-Dependent DSPP Activation - Ruixue Li; Jing Zhang; Xixi Song; Lulu Han; Mingyan Yao (Tissue Engineering and Regenerative Medicine, 2026)

Identification of a group of UDP-glycosyltransferases catalyze emodin glycosylation in Rheum officinale with substrates promiscuity - Xinyu Zhao; Xiaochen Hu; Ruixue Wang; Gang Zhang; Yuanyuan Han; Feng Yan; Mengmeng Liu (Phytochemistry, 2026)

Effects of biochar amendment on rice Fe/As uptake and growth in mine drainage-polluted paddy soil under continuous cropping - Wansheng Song; Fengzhu Liu; Chipeng Zhang; Shunyuan Zhang; Han Chen; Xiaotian Zhang; Yueyue Yang; Ruixue Zhang (Environmental Research, 2026)

Development of a Sensitive Real‐Time PCR Method for Detection of Carp Oedema Virus - Huilin He; Ruixue Feng; Siyi Guo; Bing Han; Jinshan Huang; Xu Lin; Jiyuan Yin; Defeng Zhang; Min Liu; Wen Shi (Journal of Fish Diseases, 2026)
Carp oedema virus disease (CEVD), caused by the carp oedema virus (CEV), results in significant economic losses to the common carp and koi aquaculture industry. The CEVD symptoms resemble those of koi herpesvirus (KHV) and include lethargy, swollen gills, sunken eyes, and skin haemorrhages. Consequently, the development of efficient detection methods is imperative for the prevention and diagnosis of CEVD. In this study, we developed a quantitative real‐time PCR assay for the sensitive detection of CEV infection. Specific primers were designed based on a highly conserved region within the CEV p4a gene. The assay exhibited a sensitivity that was 100‐fold greater than that of the conventional PCR technique, with high specificity, and no observed cross‐reactivity with infectious haematopoietic necrosis virus (IHNV), infectious pancreatic necrosis virus (IPNV), spring viremia of carp virus (SVCV), salmonid alphavirus (SAV), or KHV. Inter‐ and intra‐assay experiments also confirmed the method's high repeatability. In a clinical setting, it showed higher sensitivity compared to the diagnostic methods for CEVD developed by the Center for Environment, Fisheries and Aquaculture Science (CEFAS), while also significantly reducing detection costs. Consequently, the established assay could provide robust technical support for the clinical diagnosis and epidemiological investigation of CEVD.

Comparative study on degradation of PVC microplastics under four processes: mechanism, pathway and toxicological assessment - Ruixue Li; Muting Yan; Cuiming Huang; Xiaoling Wei; Lijie Xu; Lu Gan; Luyi Pan; Wei Chu; Xudai Wu; Zhenfei Han; Han Gong (Gondwana Research, 2025)

Characterization of a novel biosurfactant from Alcanivorax dieselolei and its mechanism for enhanced oil recovery in low-permeability reservoirs - Shuyuan Deng; Bo Wang; Ruixue Qu; Yuxiao Han; Cenqian Zhang; Chenyue Wang; Jian Fu; Shanshan Sun; Hao Dong; Gongze Cao; Qing You; Yuehui She; et al. (Chemical Engineering Journal, 2025)

Quantitative effects of potassium application on potato tuber yield, quality, and potassium uptake in China: A meta-analysis - Fan Zhang; Xiukang Wang; Hao He; Haochen Wang; Bolun Zhang; Shiju Liu; Ruixue Chen; Yaru Zhang; Yandong Wang; Hao Ren; Yu Wang; Juan Han (Field Crops Research, 2025)

Dual-sulfur defects decorated 1T-WS2/Cd0.5Zn0.5S heterojunctions for boosted photocatalytic hydrogen evolution - Mei Dong; Wenjun Li; Liang Geng; Ruixue Huang; Hongli Han; Yuan Liu (Journal of Environmental Chemical Engineering, 2025)

Different hydrogeological characteristics of springs associated with abandoned coal mines in well-developed karst area - Haiyang Hao; Xuanxuan Hao; Pan Wu; Xuexian Li; Zhiwei Han; Xingxing Cao; Bin Yang; Ruixue Zhang; Kaifeng Zhang; Manzhi Chen; Shihong Zhang (Journal of Hydrology, 2025)

Layered double hydroxides-engineered biochar for selective phosphate recovery by flow-electrode capacitive deionization - Jingke Song; Xin Zhao; Ruirui Liu; Songsong Zhi; Ruixue Han; Jiangzhou Xie; Jianhui Sun; Kai Jiang; Dapeng Wu (Journal of Environmental Chemical Engineering, 2025)

Identification of a novel strain of carp edema virus affecting Songpu mirror carp in Liaoning, China - Wen Shi; Bing Han; Huilin He; Ruixue Feng; Siyi Guo; Xuanyu Ren; Jinshan Huang; Xu Lin; Jiyuan Yin; Xiaonan Lv; Min Liu (Aquaculture, 2025)

Parallel RepConv network: Efficient vineyard obstacle detection with adaptability to multi-illumination conditions - Xuezhi Cui; Licheng Zhu; Bo Zhao; Ruixue Wang; Zhenhao Han; Weipeng Zhang; Lizhong Dong (Computers and Electronics in Agriculture, 2025)

Extreme climate weakens the effect of biochar in increasing yield and reducing N2O emissions - Yeye Zhang; Ruixue Chen; Liru Yao; Chun Yan; Hongxia Li; Guangxin Zhang; Michael Bahn; Fei Mo; Juan Han (Field Crops Research, 2025)

m6A methylation dynamically participates in the immune response against Vibrio anguillarum in half-smooth tongue sole (Cynoglossus semilaevis) - Suxu Tan; Wenwen Wang; Sen Han; Ruixue Zhang; Kunpeng Shi; Shaoqing Zang; Zhendong Wu; Zhenxia Sha (Fish & Shellfish Immunology, 2025)

Source apportionment of organic carbon and black carbon in the surface sediments of the Pearl River Estuary and its adjacent South China Sea: insight from stable carbon and nitrogen isotopes - Ruixue Cao; Qibin Lao; Chao Huang; Jiajun Han; Guangzhe Jin; Xuan Lu; Minggang Cai; Chunqing Chen; Fajin Chen (Frontiers in Marine Science, 2024)
Coastal estuaries and adjacent continental shelf seas constitute vital global carbon reservoirs, and the sources and transformations of organic carbon in these regions are crucial to global biogeochemical cycles and climate change. This study investigated the total organic carbon (TOC), total nitrogen (TN), black carbon (BC), and their stable carbon and nitrogen isotopes (δ 15 N TN , δ 13 C TOC , δ 13 C BC ) in the surface sediments of the Pearl River Estuary (PRE) and its adjacent northern South China Sea (NSCS) aiming to assess the impact of human activities on organic carbon dynamics in these areas. Results showed that the highest TOC concentrations occurred in the inner PRE due to intense human activities, and decreased seaward. The west side of the PRE exhibited higher TOC levels than the east side, which was attributed to differences in hydrodynamic processes and human activities. The westward flow of the Pearl River diluted water, which carried terrestrial organic matter inputs due to the influence of the Coriolis effect and intense local human activities, was a primary contributor to higher TOC levels on the west side (terrestrial source). In contrast, increased productivity and intensive mariculture activities on the east side predominated as sources of organic matter (marine source). Similar to the TOC, BC and TN sources were mainly influenced by human activities. δ 15 N TN distribution shows that TN in the east side of PRE mainly originated from industrial wastewater input from the Pearl River, while in the east side TN was mainly from domestic sewage discharge. Additionally, BC sources have shifted from primarily biomass combustion in the 1990s to fossil fuel emissions presently. Isotopic analysis revealed that over 70% of BC originated from fossil fuel inputs and C3 plant combustion, highlighting the significant influence of human activities in the PRE and adjacent NSCS, and underscoring the need for effective management and protection of the eco-environment in these regions.

Neurotoxicity induced by aged microplastics from plastic bowls: Abnormal neurotransmission in Caenorhabditis elegans - Liangzhong Li; Ruixue Ma; Yuan Yuan; Qian Yao; Yajing Han; Hanlin Cao; Jianying Qi (Science of The Total Environment, 2024)

Scorpion-inspired multi-scale contact enabled multifunctional piezoresistive pressure sensor based on hybrid nanofiber decoration - Xiaoyue Ren; Ruixue Li; Hao-Yang Mi; MiaoMiao Zhang; Qingli Tian; Xin Jing; Xiaoshuai Zhu; Jian Han; Yue Ren; Binbin Dong; Chongzhao Zhang; Chuntai Liu; et al. (Chemical Engineering Journal, 2024)

Genistein-3′-sodium sulfonate promotes brain functional rehabilitation in ischemic stroke rats by regulating astrocytes polarization through NF-κB signaling pathway - Ruizhen Liu; Yunling Yu; Qinglian Ge; Ruixue Feng; Guixiang Zhong; Li Luo; Zun Han; Tianyun Wang; Cheng Huang; Jinhua Xue; Zhihua Huang (Chemico-Biological Interactions, 2024)

Disentangling sources and transformation mechanisms of nitrogen, sulfate, and carbon in water of a Karst Critical Zone - Huijun Ye; Zhiwei Han; Pan Wu; Xuefang Zha; Xuexian Li; Enqing Hou; Yingjie Cao; Changyuan Tang; Ruixue Zhang; Jordi Sardans; Josep Peñuelas (Science of The Total Environment, 2024)

Assessment of natural resource endowment and urban-rural integration for sustainable development in Xinjiang, China - Keqiao Su; Dawei He; Ruixue Wang; Ze Han; Xiangzheng Deng (Journal of Cleaner Production, 2024)

Mg Fe- layered double hydroxides (LDHs) modified electrode enhanced capacitive deionization for simultaneous phosphorus recovery and copper ions removal - Jingke Song; Chenyang Li; Xin Zhao; Ruirui Liu; Ruixue Han; Kai Jiang; Meiqing Shi; Dapeng Wu (Journal of Environmental Chemical Engineering, 2024)

Microplastic pollution in water environment of typical nature reserves and scenery districts in southern China - Han Gong; Ruixue Li; Feng Li; Lijie Xu; Lu Gan; Jingxian Li; Haisheng Huang; Muting Yan; Jun Wang (Science of The Total Environment, 2023)

Occurrence and removal of antibiotics from aquaculture wastewater by solar-driven Fe(VI)/oxone process - Han Gong; Ruixue Li; Yanqiong Zhang; Lijie Xu; Lu Gan; Luyi Pan; Minxing Liang; Xue Yang; Wei Chu; Yuan Gao; Muting Yan (Chemosphere, 2023)

Adverse effects of silver nanoparticles on aquatic plants and zooplankton: A review - Feng Li; Ruixue Li; Fengru Lu; Lijie Xu; Lu Gan; Wei Chu; Muting Yan; Han Gong (Chemosphere, 2023)

Removal of antibiotic-resistant bacteria and genes by Solar-activated Ferrate/ Peroxymonosulfate: Efficiency in aquaculture wastewater and mechanism - Ruixue Li; Xudai Wu; Zhenfei Han; Lijie Xu; Lu Gan; Yanqiong Zhang; Fengru Lu; Hua Lin; Xue Yang; Muting Yan; Wei Chu; Han Gong (Chemical Engineering Journal, 2023)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

Toxicity of nanoplastics to aquatic organisms: Genotoxicity, cytotoxicity, individual level and beyond individual level - Han Gong; Ruixue Li; Feng Li; Xiaowen Guo; Lijie Xu; Lu Gan; Muting Yan; Jun Wang (Journal of Hazardous Materials, 2023)

Detection of microplastics in domestic and fetal pigs’ lung tissue in natural environment: A preliminary study - Han Li; Zuosen Yang; Feng Jiang; Liang Li; Yansheng Li; Minmin Zhang; Zhenzhen Qi; Ruixue Ma; Yuanyuan Zhang; Jing Fang; Xi Chen; Yihang Geng; et al. (Environmental Research, 2023)

Numerical modeling of changes in groundwater storage and nitrate load in the unconfined aquifer near a river receiving reclaimed water - Ruixue Jiang; Dongmei Han; Xianfang Song; Fandong Zheng (Environmental Science and Pollution Research, 2022)

Using stable isotopes and major ions to identify hydrological processes and geochemical characteristics in a typical karstic basin, Guizhou, southwest China - Zhiwei Han; Changyuan Tang; Pan Wu; Ruixue Zhang; Chipeng Zhang (Isotopes in Environmental and Health Studies, 2014)